Loss of Function of GALNT2 Lowers High-Density Lipoproteins in Humans, Nonhuman Primates, and Rodents - Khetarpal, Sumeet A.; Schjoldager, Katrine T.; Christoffersen, Christina; Raghavan, Avanthi; Edmondson, Andrew C.; Reutter, Heiko M.; Ahmed, Bouhouche; Ouazzani, Reda; Peloso, Gina M.; Vitali, Cecilia; Zhao, Wei; Somasundara, Amritha Varshini Hanasoge; et al. (Cell Metabolism, 2016)
Human genetics studies have implicated GALNT2, encoding GalNAc-T2, as a regulator of high-density lipoprotein cholesterol (HDL-C) metabolism, but the mechanisms relating GALNT2 to HDL-C remain unclear. We investigated the impact of homozygous GALNT2 deficiency on HDL-C in humans and mammalian models. We identified two humans homozygous for loss-of-function mutations in GALNT2 who demonstrated low HDL-C. We also found that GALNT2 loss of function in mice, rats, and nonhuman primates decreased HDL-C. O-glycoproteomics studies of a human GALNT2-deficient subject validated ANGPTL3 and ApoC-III as GalNAc-T2 targets. Additional glycoproteomics in rodents identified targets influencing HDL-C, including phospholipid transfer protein (PLTP). GALNT2 deficiency reduced plasma PLTP activity in humans and rodents, and in mice this was rescued by reconstitution of hepatic Galnt2. We also found that GALNT2 GWAS SNPs associated with reduced HDL-C also correlate with lower hepatic GALNT2 expression. These results posit GALNT2 as a direct modulator of HDL metabolism across mammals.
EVALuna2:9336